The Influences of Traditional Market Revitalization Policy on the Design Thinking Process: (Case Studies: Modern-Traditional Market in Bali) - Prabandari, Nyoman; Putra, I Nyoman Gede Maha; Triadi, I Komang Arya (Talenta Publisher, 2024)
The Revitalization Policy for Traditional Market Buildings often leads to mismatches between the designed space and its actual use. Many market facilities remain underutilised, while new informal spaces emerge in inappropriate locations. This highlights the need to reassess the design process and understand how revitalization policies impact Traditional-Modern Market planners. This research investigates the influence of existing policies on resolving design issues when modernising traditional market buildings. Using multiple case studies, specifically Badung Market and Banyuasri Market in Bali, the research collects data from design drawing archives provided by consultants and government agencies. These archival studies are compared with observations of user behaviour. Additionally, interviews with space planners, including two architectural consultants and four government officials from the Industry and Trade Service and the Public Works Service, were conducted. The qualitative analysis aims to construct the